2013
DOI: 10.1590/s1980-65742013000300017
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes about inclusion by educators and physical educators: effects of participation in an inclusive adapted physical education program

Abstract: Abstract-This study assessed the attitudes about the inclusion of students with disability by professionals in education and health, relative to their experience and training. We compared three groups: 20 teachers and trainees who worked in an adapted physical education program (GI); 75 professionals from the municipal education system of Rio Claro subdivided according to their experience-CGyes e CGno, respectively, with and without experience. We used the inventory adapted by Palla (2001) to assess participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
1
7
0
5
Order By: Relevance
“…Tellingly, Brazilian physical education teachers have expressed hesitancy about teaching students with disabilities and contend that they are not adequately prepared to do so effectively (Nascimento et al, 2007). Therefore, although more students with disabilities are being educated in inclusive classes, unprepared teachers tend to improvise pedagogical practices because of inadequate training (Mauerberg-deCastro et al, 2013). For example, Alves and Duarte (2014) reported that feelings of exclusion for students with disabilities in physical education occurred as a result of lack of adaptations presented by their physical educators.…”
Section: Introductionmentioning
confidence: 99%
“…Tellingly, Brazilian physical education teachers have expressed hesitancy about teaching students with disabilities and contend that they are not adequately prepared to do so effectively (Nascimento et al, 2007). Therefore, although more students with disabilities are being educated in inclusive classes, unprepared teachers tend to improvise pedagogical practices because of inadequate training (Mauerberg-deCastro et al, 2013). For example, Alves and Duarte (2014) reported that feelings of exclusion for students with disabilities in physical education occurred as a result of lack of adaptations presented by their physical educators.…”
Section: Introductionmentioning
confidence: 99%
“…As the student teachers had a greater possibility of contact with people with disabilities due to the different projects that the university offered at the time of the research, the participants may have acquired and developed skills and competences that made them feel more capable and able to deal with children in a context of inclusion in Physical Education classes at school (Mauerberg-decastro et al, 2013). Similarly, this perception of competence tends to generate fewer negative physiological and emotional reactions.…”
Section: Scale/dimensionmentioning
confidence: 99%
“…7, March 31, 2004) have oriented that the needs of people with disabilities, among various dimensions and populations, in order to provide physical activity, care for health and quality of life, should be contemplated. However, Physical Education teachers have identified the presence of barriers in promoting inclusion in school, since the structure and faculty are not always prepared for this (Mauerberg-decastro et al, 2013;Palla & Mauerberg-decastro, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No Brasil, nas décadas de 1980 e 1990, os governos estaduais e federais tomaram iniciativas para modernizar as leis relacionadas aos direitos das pessoas com deficiências. 6 Entretanto, apesar dos direitos de acesso à educação no ensino regular, estabelecidos em Declarações, Leis e Decretos, como: Constituição Federal do Brasil -1988; Declaração Mundial sobre Educação para todos -1990; Declaração de Salamanca -1994; Lei de Diretrizes e Bases -1996; Lei n. 9.394 -1996; Resolução CNE/CEB n˚02/2001; Política Nacional de Educação Especial na Perspectiva da Educação Inclusiva -2008; Lei n. 11.494 -2007, [7][8][9] dentre outras. O que ainda temos nos dias de hoje é uma batalha constante em oportunizar as pessoas com deficiência, o acesso à educação de qualidade.…”
Section: Tutoring In Inclusive Physical Education Classes: a Systematunclassified